2021
DOI: 10.3393/ac.2020.09.15
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Postoperative Outcomes of Single-Incision Laparoscopic Appendectomy and Three Port Appendectomy With Enhanced Recovery After Surgery Protocol for Acute Appendicitis: A Propensity Score Matching Analysis

Abstract: The objective of this study was to compare the perioperative outcomes between single incision laparoscopic appendectomy (SILA) and three port appendectomy (CLA) in enhanced recovery after surgery (ERAS) protocol. Methods: Of 101 laparoscopic appendectomy with ERAS protocol cases for appendicitis from March 2019 to April 2020, 54 patients underwent SILA with multimodal analgesic approach (group 1) while 47 patients received CLA with multimodal analgesic approach (group 2). SILA and CLA were compared with the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Early postoperative oral nutrition intake can reduce the damage of postoperative pulmonary function, restore gastrointestinal peristalsis as soon as possible, reduce activity and enhance cardiovascular function. As a new surgical concept, accelerated surgery has greatly changed the perioperative treatment of many surgical operations (8,9). However, accelerated rehabilitation surgery has been gradually applied by surgeons in clinical practice, and its safety and effectiveness in treating acute appendicitis in children have yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Early postoperative oral nutrition intake can reduce the damage of postoperative pulmonary function, restore gastrointestinal peristalsis as soon as possible, reduce activity and enhance cardiovascular function. As a new surgical concept, accelerated surgery has greatly changed the perioperative treatment of many surgical operations (8,9). However, accelerated rehabilitation surgery has been gradually applied by surgeons in clinical practice, and its safety and effectiveness in treating acute appendicitis in children have yet to be confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The LOS after a laparoscopic appendectomy varies by country, surgeon' preference, and culture. Recently, the mean LOS after a laparoscopic appendectomy for uncomplicated appendicitis ranged from 1.6 to 4.2 days in Korea [15,18] and from 0 to 3 days in other countries [19,20]. The relatively longer hospital stays in Korea probably reflect a generous national public medical insurance system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results are reliable. Some studies reported that operative time was associated with prolonged LOS after laparoscopic appendectomy [12,13,15], although the mechanism is unclear. It is well known that difficult cases require extended duration of treatment, including pneumoperitoneum, irrigation, and other surgical maneuvers, which may contribute to contamination of the abdominal cavity [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic appendectomy can be performed by a single port or conventional three-port technique. A study involving 101 patients by Kim et al [ 105 ] reported that Single-incision laparoscopic appendectomy (SILA) reduced the length of hospitalization (1.2 ± 0.8 d vs 1.6 ± 0.8 d, P = 0.037) vs three-port appendectomy[ 105 ]. Systematic reviews and meta-analyses report that SILA is associated with a shorter length of hospital stay but longer operation duration and increased risk of open conversion[ 106 , 107 ].…”
Section: Management Of Appendicitismentioning
confidence: 99%